A single-cell transcriptomic landscape of mouse testicular aging - Zhang, Wei; Xia, Siyu; Xiao, Wei; Song, Yali; Tang, Li; Cao, Min; Yang, Jing; Wang, Shuang; Li, Zhijie; Xu, Chengchao; Liu, Jianqiao; Zhao, Shanchao; et al. (Journal of advanced research, 2023)
[Display omitted] •The first single-cell transcriptomic atlases of testes of young and old mice were constructed.•Revealed aging-associated heterogenous differentially expressed genes in mouse testes.•Discovered aging-associated dysregulation of multiple biological processes in mouse testes.•Aging disrupted balance of undifferentiated and differentiated spermatogonia stem cells in spermatogonia.•Aging increased a subtype of aging-specific macrophages. Advanced paternal age of reproduction is an increasing trend, especially in developed countries and areas. This trend results in elevated risks of adverse reproductive outcomes such as reduced fertility rates, increased pregnancy loss, and poor childhood health. Yet, a systematic profiling of aging-associated molecular and cellular alterations in testicular tissue is still missing. We aimed to dissect aging-associated molecular characteristics in testes of mice. Single-cell transcriptomic sequencing and analysis were conducted in testes of young (2 months old) and old mice (24 months old). Immunofluorescences and immunochemistry were used to characterize aging-associated phenotypes and verify single cell sequence results. Here, we constructed the first single-cell transcriptomic atlases of testes of young and old mice. In-depth dissection of aging-dependent transcriptional alterations in specific cell types revealed multiple dysregulated biological processes such as increased ‘senescence-associated secretory phenotype’ and ‘inflammation’, which were major aging-associated characteristics. Further analysis of aging-related differentially expressed genes uncovered a disrupted balance of undifferentiated and differentiated spermatogonia stem cells in spermatogonia, indicative of a potential role of spermatogonia stem cells in aging-associated subfertility. Importantly, for the first time, our results identified an increased subtype of aging-specific macrophages, which may contribute to a hostile proinflammatory microenvironment during testicular aging. Taken together, our findings depict the distinct single-cell transcriptional features of the aged mouse testes and provide enormous resources for a comprehensive understanding of the cell-type-specific molecular mechanisms underlying mouse testicular aging, which may shed light on developing novel potential diagnostic biomarkers and therapeutic targets for age-associated male subfertility.